2017
DOI: 10.1103/physreva.95.062307
|View full text |Cite
|
Sign up to set email alerts
|

Estimating phase with a random generator: Strategies and resources in multiparameter quantum metrology

Abstract: Quantum metrology aims to exploit quantum phenomena to overcome classical limitations in the estimation of relevant parameters. We consider a probe undergoing a phase shift ϕ whose generator is randomly sampled according to a distribution with unknown concentration κ, which introduces a physical source of noise. We then investigate strategies for the joint estimation of the two parameters ϕ and κ given a finite number N of interactions with the phase imprinting channel. We consider both single qubit and multip… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 70 publications
0
22
0
Order By: Relevance
“…estimation strategies. These two strategies generate different precision scalings in the count resource [276][277][278] and the time resource 204,208,218 . However, no clear results have been found that determine when either strategy should be preferred.…”
Section: Distributed Quantum Sensingmentioning
confidence: 99%
“…estimation strategies. These two strategies generate different precision scalings in the count resource [276][277][278] and the time resource 204,208,218 . However, no clear results have been found that determine when either strategy should be preferred.…”
Section: Distributed Quantum Sensingmentioning
confidence: 99%
“…Indeed, the capability of obtaining quantum-enhanced performances in the multiparameter case is particularly relevant [9], since a large variety of estimation problems involve more than a single physical quantity. Notable examples are phase imaging [10][11][12], measurements on biological systems [13,14], magnetic field imaging [15], gravitational waves parameters estimation [16,17], sensing technologies [18,19], quantum sensing networks [20], quantum process tomography [21][22][23][24] and state estimation [25].…”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown that a super-extensive growth of the frequency sensitivity may still be attained under time-inhomogeneous, phase-covariant noise [26][27][28][29][30], and even more generic Ohmic dissipation [31], noise with a particular geometry [32,33], or setups related to quantum error correction [34][35][36]. See also [37,38] which question the role of entanglement in such schemes and give advice on practical implementations. In general, these studies have shown that, while the 1/n precision scaling in frequency estimation may not be available in the presence of noise, it is possible to achieve a scaling that goes as n 1 3 4 , n 1 5 6 , or n 1 7 8 depending on the details of the problem.…”
Section: Introductionmentioning
confidence: 99%